Número mínimo de repetições de plantas por parcela e de avaliações e seleção precoce em testes clonais de eucalipto - Araujo, Marcio José de [UNESP] (2015)
The objectives of this study were to determine the optimal number of replications of plants per plot and the number of evaluations for growth traits and the viability of early selection in eucalyptus clonal tests, in order to infer reliably on the actual value of the individual the environment that it is, thus allowing precision in estimates of genetic parameters and selection gains. The data of three eucalyptus hybrid clonal tests, evaluating the diameter at breast height (DBH), height and wood commercial volume. The experimental design for the three clonal tests was randomized blocks with six replications, two tests with 30 clones and one with ten clones, with six or ten plants per plot. For full features were estimated the repeatability coefficient, the optimal number of replications of plants per plot and evaluations to infer about the real value of the individual and genetic gains for the characteristic volume in adulthood (72 months) with the early selection of individuals. Eucalyptus clonal tests, intended to improve in the short term, the objective of selection is to maximize the gain in the current generation for both traits in this work (diameter, height and volume) both require 3 replications with 6 plants per plot and evaluated in three ages for a selective accuracy around 90%. The selection of superior individuals in juvenile ages (over two years) in eucalypt clonal tests allows genetic gain in rotation age, being advantageous especially selection for diameter at breast height (DBH) to obtain future gains and indirectly to the volume character